Cognitive Biases and Strategic Decision Processes: An Integrative Perspective - Das, T.K.; Teng, Bing‐Sheng (Journal of Management Studies, 1999)
Previous studies have not adequately addressed the role of cognitive biases in strategic decision processes. In this article we suggest that cognitive biases are systematically associated with strategic decision processes. Different decision processes tend to accentuate particular types of cognitive bias. We develop an integrative framework to explore the presence of four basic types of cognitive bias under five different modes of decision making. The cognitive biases include prior hypotheses and focusing on limited targets, exposure to limited alternatives, insensitivity to outcome probabilities and illusion of manageability. The five modes of strategic decision making are rational, avoidance, logical incrementalist, political and garbage can. We suggest a number of key propositions to facilitate empirical testing of the various contingent relationships implicit in the framework. Lastly, we discuss the implications of this framework for research and managerial practice.